Strengthening Green Loyalty: How Green Marketing, Green Perceived Value, and Environmental Concern Drive Green Satisfaction (A Study of Uniqlo’s Consumer in Bandung Metropolitan) - Septiarini, Eka; Djulius, Horas; Juhana, Dudung (Research Collaboration Community (RCC), 2025)
The objective of this study is to identify, examine, and analyze the influence of green marketing on green customer satisfaction, the influence of green perceived value on green customer satisfaction, the influence of environmental concern on green satisfaction, and the influence of green satisfaction on green customer loyalty of Uniqlo consumers in Bandung Metropolitan. Data were collected from respondents aged between 17 and 55 years old, residing in the Bandung Metropolitan area, and having purchased Uniqlo's green products at least twice in the past year. The analysis was performed using Lisrel - Structural Equation Modeling version 8.8. The findings reveal that green marketing, green perceived value, and environmental concern simultaniously contribute 73.6% to green customer satisfaction with Uniqlo in Bandung Metropolitan, while the remaining 26.4% is influenced by other variables. Partially, green marketing contributes 18.5%, green perceived value 24.4%, and environmental concern 30.7% to green satisfaction. Additionally, green satisfaction has been proven to have a significant influence of 79.9% on green loyalty among Uniqlo consumers in Bandung Metropolitans.